2021
DOI: 10.1007/s10439-021-02723-0
|View full text |Cite
|
Sign up to set email alerts
|

Impact Performance Comparison of Advanced Snow Sport Helmets with Dedicated Rotation-Damping Systems

Abstract: Rotational acceleration of the head is a principal cause of concussion and traumatic brain injury. Several rotation-damping systems for helmets have been introduced to better protect the brain from rotational forces. But these systems have not been evaluated in snow sport helmets. This study investigated two snow sport helmets with different rotation-damping systems, termed MIPS and WaveCel, in comparison to a standard snow sport helmet without a rotation-damping system. Impact performance was evaluated by ver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 33 publications
0
17
0
Order By: Relevance
“…2,7 This has promoted the development of various new helmets incorporating rotational acceleration testing and rotational damping technology that may decrease concussion incidence or magnitude. 98,99 For example, Hoshizaki et al 98 employed drops onto a 45° anvil to simulate the rotational dynamics of head impacts, showing that two helmets fitted with rotational damping technologies better mitigated rotational acceleration compared to a standard helmet. DiGiacomo et al 99 similarly used drops onto a 45° anvil to show that rotational damping-based snow helmets significantly reduce rotational acceleration and concussion probability compared to standard helmets.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…2,7 This has promoted the development of various new helmets incorporating rotational acceleration testing and rotational damping technology that may decrease concussion incidence or magnitude. 98,99 For example, Hoshizaki et al 98 employed drops onto a 45° anvil to simulate the rotational dynamics of head impacts, showing that two helmets fitted with rotational damping technologies better mitigated rotational acceleration compared to a standard helmet. DiGiacomo et al 99 similarly used drops onto a 45° anvil to show that rotational damping-based snow helmets significantly reduce rotational acceleration and concussion probability compared to standard helmets.…”
Section: Discussionmentioning
confidence: 99%
“…98,99 For example, Hoshizaki et al 98 employed drops onto a 45° anvil to simulate the rotational dynamics of head impacts, showing that two helmets fitted with rotational damping technologies better mitigated rotational acceleration compared to a standard helmet. DiGiacomo et al 99 similarly used drops onto a 45° anvil to show that rotational damping-based snow helmets significantly reduce rotational acceleration and concussion probability compared to standard helmets. More testing of the different rotational damping helmets is necessary to see which provides the most effective protection against concussions.…”
Section: Discussionmentioning
confidence: 99%
“…[16,17,28] Similarly, WaveCel technology has been introduced in bicycle and snow sport helmets to mitigate rotational forces by providing a cellular energy mitigation system. MIPS and WaveCel technologies have been shown to significantly reduce rotational head acceleration and the corresponding TBI risk in bicycle [14] and snow [15] helmets, but they have not been tested in construction helmets.…”
Section: J O U R N a L P R E -P R O O Fmentioning
confidence: 99%
“…Post et al 19 and Rowson et al 20 reported a weak relationship between peak rotational and linear accelerations for head impacts. While several test methods have been employed, to date no cycling helmet test standard includes a rotational performance criterion 10 , 12 , 14 , 21 – 27 . A proposed high friction impact test protocol was used to measure a helmets capacity to manage rotational acceleration.…”
Section: Introductionmentioning
confidence: 99%